The Novel iMPACT Tool and Quadrant Protocol for Peri-Implantitis: Surface Refinement and Re-Osseointegration Validated by SEM/EDS and Long-Term Clinical Case Reports - Gustavo Vicentis Oliveira Fernandes; Bruno Gomes dos Santos Martins; Juliana Campos Hasse Fernandes; Yankel Gabet; Amiram Vizanski (Medicina)
Background and Objectives: The goal of this study was to introduce a novel device, the iMPACT implant planer, designed to machine (create a complete smooth surface) contaminated implant surfaces intraorally, promoting peri-implant tissue healing and possible re-osseointegration, and the new Quadrant protocol, evaluating them in vitro and clinically. The null hypothesis was that there would be no improvement in the clinical parameters for the implants with peri-implantitis (PI) treated with the new protocol and tool. Materials and Methods: The Quadrant protocol was used in conjunction with the iMPACT tool, which primarily functions to remove biofilm and microbial contaminants from the exposed implant surface, while simultaneously preparing the surface through standardized implantoplasty, thereby enhancing the potential for re-osseointegration. An in vitro analysis was developed, and three medium/long-term cases were presented, detailing the procedures and outcomes. Results: The in vitro assessment showed smooth surfaces after treatment. Different areas presented minimal particles (<1 μm) on the implant surface, with a high content of titanium (Ti) and tungsten (W). In case 1, severe and advanced peri-implantitis around implants #46 and #47 was found. A combination of resective (Quadrant + iMPACT) and regenerative surgery was used for treatment, along with a buccal single flap (BSF). Significant clinical and radiographic improvements were observed at 14 and 43 months postoperatively, including vertical bone gain with re-osseointegration and stable probing depths (PDs). In the second case, a severe PI and prosthesis instability were observed. Resective (Quadrant + iMPACT) and regenerative procedures were applied. At 3 and 12 months postoperatively, clinical and radiographic evaluations demonstrated significant improvements with re-osseointegration, including PDs reduced to 0–1 mm and a vertical bone gain of approximately 6.5 mm. In case 3, mandibular implants from 42 to 47 exhibited inflammation, suppuration, and moderate-to-severe bone loss. Just resective surgery (Quadrant + iMPACT), without grafting, was performed. At 6- and 12-month follow-ups, clinical and radiographic assessments showed the resolution of inflammation, stable bone levels, and healthy peri-implant gingiva. Conclusions: Favorable outcomes were achieved using the iMPACT and Quadrant protocols in the three clinical cases, resulting in re-osseointegration when combined with regenerative procedures. The favorable medium/long-term outcomes achieved, despite the patient’s complex medical history and, at times, inconsistent oral hygiene, underscore the potential efficacy of such interventions.